Survey-based structural budget balances - Marcell Göttert; Timo Wollmershäuser (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
The budget dispute between Italy and the European Commission in 2018 gave new impetus for the debate about the reliability of output gap estimation methods and their use for calculating structural budget balances. In this paper we review the main properties of the mainstream approaches and compare their performance with structural budget balances, whose calculation is based on a business survey. Our main result is that while the survey-based measure is highly correlated with the existing structural budget balances which are calculated based on some estimates of the output gap, it is significantly less revised over time and almost unbiased. Moreover, the survey-based measure could be easily implemented into the existing EU fiscal rules without any major changes.
Keywords: E32; E62; H62; H68; 330; fiscal rules; cyclical adjustment; output gaps; real time data